Transcriptome Profiling of Staphylococcus aureus Associated Extracellular Vesicles Reveals Presence of Small RNA-Cargo - Joshi, Bishnu; Singh, Bhupender; Nadeem, Aftab; Askarian, Fatemeh; Wai, Sun Nyunt; Johannessen, Mona; Hegstad, Kristin (Frontiers in Molecular Biosciences, 2021)
Bacterial extracellular vesicles (EVs) have a vital role in bacterial pathogenesis. However, to date, the small RNA-cargo of EVs released by the opportunistic pathogen Staphylococcus aureus has not been characterized. Here, we shed light on the association of small RNAs with EVs secreted by S. aureus MSSA476 cultured in iron-depleted bacteriologic media supplemented with a subinhibitory dosage of vancomycin to mimic infection condition. Confocal microscopy analysis on intact RNase-treated EVs indicated that RNA is associated with EV particles. Transcriptomic followed by bioinformatics analysis of EV-associated RNA revealed the presence of potential gene regulatory small RNAs and high levels of tRNAs. Among the EV-associated enriched small RNAs were SsrA, RsaC and RNAIII. Our finding invites new insights into the potential role of EV-associated RNA as a modulator of host-pathogen interaction.